Treatment of gingival hyperpigmentation for esthetic purposes by Nd:YAG laser: Report of 4 cases - Phimon Atsawasuwan (2018)
Gingival hyperpigmentation may cause esthetic problems and embarrassment, especially in patients with a gummy smile. This report presents the use of the Hd:YAG laser for gingival depigmentation. Four cases, 3 females and 1 male, ages between 24 to 28 years old, presented with the same chief complaint of unesthetic gingiva caused by melanin hyperpigmentation. The Nd:YAG laser was set at 6 watts, 60 millijoules per pulse, and 100 pulses per second. The procedures were performed with contact mode in all pigmented areas by using a handpiece with a 320 μm diameter fiber optic. Ablation of the gingival hyperpigmented areas were accomplished without any bleeding complications or significant postoperative pain. Three to 4 weeks after the procedures, the hyperpigmented gingiva appeared healthy, pink, and firm. No recurrence of hyperpigmentation had been found in 11 to 13 months of follow-up. However, in delicate areas such as the marginal gingiva, the Nd-VAG laser should be used cautiously.